La sociología en el Perú. Trayectoria histórica y desafíos teóricos* - Mejía Navarrete, Julio (2005)
This work is a synthesis of the evolution of the sociology in Peru since its incorporation as a university cathedra in 1896. A discourse is build in order to link with the development changes of the modernity in the country and, at the same time, is supported with the theoretical debate resulting from the slow institutionalization process of the discipline and the emergent higher awareness of the plurality of paradigms, methodological perspectives and interpretive possibilities on social reality in recent years